Cost–utility analysis and otolaryngology. Issue 2 (10th February 2014) - Hamilton, D; Hulme, C; Flood, L; Powell, S
Abstract: As providers of health care, we face increasing demand on our limited, indeed diminishing, resources. Economic appraisal of our interventions means assessing the trade-off between effectiveness, efficiency and equity. When rationing becomes inevitable, calculation of utility values is a valuable decision-making tool. This paper reviews objective measures of patient benefit, such as quality of life, and focuses on their application within otolaryngology.